ADAM-17 is expressed on rheumatoid arthritis fibroblast-like synoviocytes and regulates proinflammatory mediator expression and monocyte adhesion - Ishii, Sho; Isozaki, Takeo; Furuya, Hidekazu; Takeuchi, Hiroko; Tsubokura, Yumi; Inagaki, Katsunori; Kasama, Tsuyoshi (Arthritis Research & Therapy, 2018)
To examine the expression of ADAM-17 in rheumatoid arthritis (RA) biological fluids and the role it plays in monocyte adhesion to RA fibroblast-like synoviocytes (FLSs). ADAM-17 expression was measured by enzyme-linked immunosorbent assays (ELISAs) in serum from normal (NL) subjects, osteoarthritis (OA) patients, and RA patients. We also analyzed the correlation between ADAM-17 and disease activity score 28 (DAS28) in RA. To determine expression of ADAM-17 in RA synovial tissues (STs) and RA FLS, we performed immunofluorescence analyses. To determine the role of ADAM-17 in RA, we transfected RA FLSs with small interfering RNA (siRNA) against ADAM-17. THP-1 adhesion to ADAM-17 siRNA-transfected RA FLSs was measured. Finally, adhesion molecules on ADAM-17 siRNA-transfected RA FLSs were measured using cell surface ELISAs. ADAM-17 in RA serum was significantly higher than that in NL and OA serum and correlated with DAS28. ADAM-17 in RA synovial fluids was higher than that in OA synovial fluids. ADAM-17 was expressed on RA cells lining STs and RA FLSs. THP-1 adhesion to ADAM-17 siRNA-transfected RA FLSs was decreased compared with that to control siRNA-transfected RA FLSs. ICAM-1 on TNF-α-stimulated ADAM-17 siRNA-transfected RA FLSs was significantly decreased compared with that on control siRNA-transfected RA FLSs. These data indicate that ADAM-17 is expressed on RA STs and plays a role in RA inflammation by regulating monocyte adhesion to RA FLSs. ADAM-17 might be an important inflammatory mediator in inflammatory diseases such as RA.